Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity. Issue 18 (17th September 2018) - Yang, Jing; Li, Yong-Chao; Zhou, Xiu-Ren; Xu, Xin-Juan; Fu, Qing-Yun; Liu, Chang-Zhong
Abstract: A new monoterpenoid, 7-acetyl-8, 9-dihydroxy thymol (1 ), together with a known one 7, 8-dihydroxy-9-buyryl thymol (2 ), were isolated from the dried flower buds of Lonicera japonica Thunb. Their structures were elucidated on the basis of extensive 1D and 2D NMR spectroscopic data analyses. The potential antibacterial effects of these compounds on Staphylococcus aureus, Escherichia coli, Micrococcus luteus, and Bacillus cereus were evaluated. Interestingly, both compounds1 and2 exhibited significant antibacterial activities with IC50 values range from 27.64 ± 2.26 to 128.58 ± 13.26 μg/mL. Abstract :